Decreased susceptibility of Streptococcus anginosus to vancomycin in a multispecies biofilm is due to increased thickness of the cell wall. (12th June 2018) - Tavernier, Sarah; Sass, Andrea; De Bruyne, Michiel; Baeke, Femke; De Rycke, Riet; Crabbé, Aurélie; Vandecandelaere, Ilse; Van Nieuwerburgh, Filip; Coenye, Tom
Abstract: Background: Streptococcus anginosus, Pseudomonas aeruginosa and Staphylococcus aureus are often co-isolated from the sputum of cystic fibrosis patients. It was recently shown that S. anginosus is protected from the activity of vancomycin when it grows in a multispecies biofilm with P. aeruginosa and S. aureus . Objectives: Elucidating the underlying cause of the reduced susceptibility of S. anginosus to vancomycin when growing in a multispecies biofilm with P. aeruginosa and S. aureus . Methods: The transcriptome of S. anginosus growing in a multispecies biofilm was compared with that of a S. anginosus monospecies biofilm. Subsequently, transmission electron microscopy was performed to investigate changes in cell wall morphology in S. anginosus and S. aureus in response to growth in multispecies biofilm and to vancomycin treatment. Results: S. anginosus responds to growth in a multispecies biofilm with induction of genes involved in cell envelope biogenesis. Cell walls of S. anginosus cultured in a multispecies biofilm were thicker than in a monospecies biofilm, without antibiotic challenge. S. aureus, when cultured in a multispecies biofilm, does not respond to vancomycin treatment with cell wall thickening. Conclusions: Growth in multispecies biofilms can have an impact on the expression of genes related to cell wall synthesis and on the cell wall thickness of S. anginosus .